65.8k views
5 votes
Which of the following equations are equations of circles? Choose all that apply.

Which of the following equations are equations of circles? Choose all that apply.-example-1
User Sudhin
by
4.7k points

2 Answers

1 vote

Answer:

Number 3 and Number 4

Explanation:

User Rahul Satal
by
5.3k points
4 votes

Answer:


x^(2)+y^(2)+2x+10y-5=0


3x^(2)+3y^(2)+12x+30y-6=0

Explanation:

we know that

The equation of a circle ion standard form is equal to


(x-h)^(2) +(y-k)^(2)=r^(2)

where

(h,k) is the center and r is the radius

Verify each case

case 1) we have


(x+5)^(2) +(y+2)^(2)=-4

The radius squared cannot be a negative number


r^(2)\\eq -4

therefore

This equation is not the equation of a circle

case 2) we have


2x^(2)+y^(2)+15x-y+3=0

Group terms that contain the same variable, and move the constant to the opposite side of the equation


(2x^(2)+15x)+(y^(2)-y)=-3

Factor the leading coefficient of each expression


2(x^(2)+7.5x)+(y^(2)-y)=-3

Complete the square twice. Remember to balance the equation by adding the same constants to each side.


2(x^(2)+7.5x+14.0625)+(y^(2)-y+0.25)=-3+28.125+0.25


2(x^(2)+7.5x+14.0625)+(y^(2)-y+0.25)=25.375

Rewrite as perfect squares


2(x+3.75)^(2)+(y-0.5)^(2)=25.375

This equation is not the equation of a circle

case 3) we have


x^(2)+y^(2)+2x+10y-5=0

Group terms that contain the same variable, and move the constant to the opposite side of the equation


(x^(2)+2x)+(y^(2)+10y)=5

Complete the square twice. Remember to balance the equation by adding the same constants to each side.


(x^(2)+2x+1)+(y^(2)+10y+25)=5+1+25


(x^(2)+2x+1)+(y^(2)+10y+25)=31

Rewrite as perfect squares


(x+1)^(2)+(y+5)^(2)=31

This equation represent the equation of a circle

case 4) we have


3x^(2)+3y^(2)+12x+30y-6=0

Group terms that contain the same variable, and move the constant to the opposite side of the equation


(3x^(2)+12x)+(3y^(2)+30y)=6

Factor the leading coefficient of each expression


3(x^(2)+4x)+3(y^(2)+10y)=6

Complete the square twice. Remember to balance the equation by adding the same constants to each side.


3(x^(2)+4x+4)+3(y^(2)+10y+25)=6+12+75


3(x^(2)+4x+4)+3(y^(2)+10y+25)=93

Rewrite as perfect squares


3(x+2)^(2)+3(y+5)^(2)=93

Divide by 3 both sides


(x+2)^(2)+(y+5)^(2)=31

This equation represent the equation of a circle

case 5) we have


x^(2)-y^(2)+20x+2y+9=0

Group terms that contain the same variable, and move the constant to the opposite side of the equation


(x^(2)+20x)-(y^(2)-2y)=-9

Complete the square twice. Remember to balance the equation by adding the same constants to each side.


(x^(2)+20x+100)-(y^(2)-2y+1)=-9+10-1


(x^(2)+20x+100)-(y^(2)-2y+1)=0

Rewrite as perfect squares


(x+10)^(2)-(y-1)^(2)=0

This equation is not the equation of a circle

User Frank Ockenfuss
by
4.8k points